Synthesis of Iron Oxide (Fe3O4) magnetic nanocrystals by green chemistry approach - W.S., Chiu; S.X., Too; Daud, S.N.H; Rashid, N.M.A.; M.Y., Chia; Rahman, S.A.; Suhaimi Bakar, A.; Aspanut, Z.; P.S., Khiew; T.K., Tan; Radiman, S.; Abd-Shukor, R.; et al. (Universiti Kebangsaan Malaysia, 2014)
In the present study, we report the size distribution study on the iron oxide (Fe3O4) magnetic nanocrystals (NCs), which have been synthesized by using green chemistry approach with palm-oil based carboxylic compound (oleic acid) as capping ligands. The Fe3O4 NCs were prepared by one pot reaction under non-hydrolytic approach. With the assistance of oleic acid that plays the role as effective capping-ligands, we showed that the Fe3O4 NCs that are highly monodispersed in size and shape can be synthesized by scrupulously controlling the reaction time. The diameter of Fe3O4 NCs can be tuned within the range of 4.0-18.0 nm and exhibit very uniform morphology, which are spherical in shape. Current synthetic approach offers a cheap, environmentally benign and excellent repeatability route in large-scale production of high-quality magnetic Fe3O4 NCs if compared to the preceding reports.